Investigating the State of Flowering and Fruit Formation of Some Olive Cultivars under the Stress of Low Irrigation and Salicylic Acid Foliar Application - Rahmatollah Gholami; Isa Arji; Narjes Fahadi Hoveizeh (Agrotechniques in Industrial Crops)
In order to investigate the state of flowering and fruit formation of olive Conservalia, Zard and Amphisis cultivars under the influence of salicylic acid foliar application and under-irrigation stress in the Dalaho olive research station (longitude of 45˚, 51΄ E and latitude of 34˚, 30΄ N and the height of sea level 581m) of Kermanshah province, a field factorial experiment based on randomized complete block design with three replications and three factors (salicylic acid concentrations, Irrigation regimes and olive cultivars) was carried out in 2017 and 2018. Two stages of complete spraying of olive trees with salicylic acid at zero concentrations were performed as control (water spraying), 1.5 and 3 mM, before flowering and before the rapid growth of fruit. Irrigation treatments, including irrigation of 100% (control), 75% and 50% of the water requirement of olive trees during the season, were applied with drip irrigation system. The experimental material of this study was 17-year-old trees of three cultivars of olive cultivars. Each experimental unit consisted of two trees. Care and maintenance of trees were applied equally in all treatments. Notes on the characteristics of flowering and fruit formation, including the number of inflorescences in a branch, the number of flowers in an inflorescence, the length of an inflorescence, the number of perfect flowers in an inflorescence, the length of a flowering branch, the number of fruits in a branch, the number of perfect flowers in Branch and percentage of fruit formation (one month before harvest) were calculated based on complete flower in the branch in different treatments and different cultivars. The results of this research showed that foliar spraying of salicylic acid at a concentration of 3 mM in two growth stages before flowering and before the start of rapid fruit growth of the three studied olive cultivars moderated the effects of water stress. On the other hand, due to the decrease in the amount of irrigation water, the number of inflorescences in the branch, the number of perfect flowers in the inflorescence and the percentage of fruit formation decreased.